Assessing Business and Financial Risks: A Case Study of Sapura Energy Bhd in the Oil and Gas Industry - Ikmal Arif Mohamad Amin; Abdul Razak Abdul Hadi (Indonesian Journal of Business, Accounting and Management (IJBAM), 2023)
The oil and gas industry has been an engine room for economic growth in Malaysia due to its contributions to nation-building in the past 40 years. The main objective of this research is to investigate the root causes of Sapura Energy Bhd's central problems and recommend some best solutions. For the financial year that ended January 31, 2022, this giant oil and gas services company officially registered a tremendous loss of RM 8.9 billion, and the company is expected to suffer a more considerable loss for the current financial year. If they fail to resolve the financial crisis soonest, the company will likely go bankrupt soon. From the literature review, the Trade-off Theory seems fit to elaborate on the financial conditions of Sapura Energy Bhd. Sapura Energy operates in 20 countries and manages a workforce of 13,000 globally. The study extracts documentary evidence from financial reports and deploys descriptive statistics analysis to understand Sapura Energy’s financial profiles and competitive edges. This study also deploys descriptive statistics and trend analysis to understand Sapura Energy’s financial profiles and competitive edges. Sapura is one of the local pioneers that provides engineering services in the entire value chain for oil and gas exploration, development, and production. Sapura Energy was a national pride once as it was geared towards becoming a sustainable global energy and engineering solutions company. However, Sapura Energy’s underperformance for the past 10 years has become debatable. Sapura is experiencing a burdensome debt from large overdue payments to vendors and some operational issues exacerbated by the COVID-19 pandemic from 2020 to 2021. Sapura should consider downsizing its business operations and recalibrating its capital structure to mitigate most business and financial risks.